Comparison of the effect of different factors on shear bond strength of denture teeth to thermoplastic resin and heat polymerized acrylic resin (In vitro study) (Journal of Hama University, 2022)
Background: Acrylic teeth debonding from the denture-base resin is a frequent complication in daily practice.Objectives: This study was conducted to investigate the effect of two types of chemical and mechanical treatments on the bonding strength of acrylic teeth with two types of denture-base resins (heat-cured acrylic resin, thermoplastic resin), and to compare the effect of two types of disinfectant solutions (chlorhexidine gluconate 0.12%, sodium hypochlorite 0, 5%) with distilled water on the bonding strength of acrylic teeth with their denture bases.Materials and methods: This study included 96 upper first molars that were fixed on cylindrical bases of resin, divided into two groups according to the type of denture-base resin (heat-cured acrylic resin, thermoplastic resin), then each group was divided into two subgroups according to the method of surface treatment of the ridge lap area of denture teeth, and each subgroup was divided into 3 secondary subgroups due to type of immersion solution. After immersion, Shear bond strength testing was performed at the resin/tooth interface in a universal testing machine at a 1 mm/min crosshead speed. Data were analyzed using one-way ANOVA (α = 0.05).Results: Analysis of shear bond strength showed that there were no statistically significant differences between subgroups immerged in chlorhexidine gluconate 0.12% and sodium hypochlorite 0.5%, whether for heat-cured acrylic resin or thermoplastic resin, and their effect was similar to distilled water. Also, there were no statistically significant differences with or without the application of monomer on the ridge lap area of denture teeth for heat-cured acrylic resin samples. As for the mechanical treatments of thermoplastic samples, there were statistically significant differences.Conclusions: disinfectant solutions did not affect the bond strength of acrylic denture teeth either with heat-cured acrylic resin or thermoplastic resin. Also, wetting the ridge lap area of acrylic teeth did not affect the bond strength with heat-cured acrylic resin. The shape of the mechanical adjustment of the ridge lap area of acrylic teeth affected the bond strength with the thermoplastic resin, as the shape consisting of a hole and two grooves was better in terms of increasing the bonding strength compared to the shape consisting of only a hole.
Keywords: Acrylic teeth, heat-cured acrylic resin, thermoplastic resin, surface treatment, chlorhexidine, sodium hypochlorite.